Pemikiran Hadis Kaum Modernis Indonesia : (Analisis Pemikiran Hadis Soekarno) - Anshori, Muhammad (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2024)
This paper analyzes Soekarno’s thoughts on hadith. Hadith studies that have developed so far are still Arab-oriented, rarely in the context of Indonesia. Using the descriptive-analytical method, this paper tries to explain Soekarno's hadith thoughts that are scattered in several of his books. Soekarno is known as a modernist thinker who is critical in reading religious discourses, including hadith. Among the themes of hadith studies raised by Soekarno in this paper are the importance of hadith studies, ḍa’īf hadith, and the methods of understanding hadith